Newborn Midwifery Care For Ny "H" Baby With Low Birth Weight (BBLR) At Bungi Health Center - Harmita; Sitti Aisyah Ansi; Wa Ode Nurul Mutia (International Journal of Multidisciplinary Learners, 2025)
Background: Low birth weight is a condition when a baby is born weighing less than 2500 grams. This LBW condition will have a negative impact on the baby's growth and development in the future. Objectives: This Final Assignment Report aims to carry out "Newborn midwifery care for baby Mrs. "H" with low birth weight at the Bungi Health Center, Baubau City. Method: using an approach with the 7-step midwifery care management method of Varney and Soap. Data collection techniques using interview techniques, physical examinations and documentation studies. Subject: the subjest in this study were babies with low birth weight at the bungi community health center, baubau city. Results: from a case study obtained from Mrs “H”, with low birth weight (LBW), namely the general condition of the baby is good, weight 2.400 gr, body length 48 cm, chest circumference 29 cm, female gender, vital signs heart rate 145x/minute, temperature 36.5o c. implementation of midwifery care, namely approaching the mother and family, monitoring vitals signs and progress. Conclusion : from the care of By Ny "H" has been obtained proper midwifery care so that the problem of low birth weight has been resolved. Suggestion for clients to breastfeed their babies as often as possible.